Effects of diagenesis on quality of deep dolomite reservoirs: A case study of the Upper Cambrian Xixiangchi Formation in the eastern Sichuan Basin, China - Ren, Guanxiong; Qin, Qirong; Qin, Zhangjin; Guo, Yanbo; Ye, Zhaoyang (Frontiers in Earth Science, 2022)
With the Upper Cambrian Xixiangchi Formation in the eastern Sichuan Basin as the target, this study investigates various diagenetic events during different diagenetic stages in deep dolomite reservoirs, accompanied by evaluations of their effects upon the formation and evolution of the reservoir rock. A series of experiments are implemented on core and outcrop samples, including petrologic analysis, cathode luminescence microscopy, fluid inclusion analysis, rare earth and trace element investigation, and carbon and oxygen isotope test. During the syn-diagenetic stage, dolomitization is closely related to evaporation concentration and seepage reflux of high-salinity seawater, which facilitates the reservoir rock development by greatly enhancing the reservoir permeability. Meanwhile, a small number of secondary pores are generated in the sediments that are subjected to episodic atmospheric exposure and thus affected by meteoric water. During the eogenetic stage, recrystallization transforms part of the granular dolomite into the crystalline dolomite with or without the phantom of the grain texture. It also to some extent alters the pore structure of the original rock and improves the effective primary porosity. Thus, recrystallization is considered a key factor in the formation of the crystalline dolomite reservoir rock. However, compaction, cementation, and filling lead to the loss of massive early-formed primary pores and some secondary pores. The telogenetic burial karstification, related to organic matter maturation, is the most direct control factor of the effective reservoir space formation, and its alteration effect upon the reservoir rock is related to the eogenetic process. This research helps to better identify the effects of various diagenetic processes during different diagenetic stages upon the formation and evolution of the deep dolomite reservoir rock, and it also helps analyze the relationships among these diagenetic processes. The findings of this research provide valuable references for investigating the formation mechanism of the deep dolomite reservoir rock in the Sichuan Basin.